2023
DOI: 10.1007/s11757-023-00765-9
|View full text |Cite
|
Sign up to set email alerts
|

Structural differences in psychopathy between women and men: a latent modeling perspective

Abstract: Research on sex differences in psychopathy indicates that men generally exhibit higher psychopathy scores than women. Measurement equivalence is an important prerequisite for the investigation of mean differences, but is often neglected for psychopathy instruments. The current research provides a systematic qualitative review of the pertinent literature on measurement invariance between men and women for several rater-based and self-report-based psychopathy assessments. Based on 28 studies, we found that the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 63 publications
0
0
0
Order By: Relevance
“…A recent study found that measures of everyday sadism are in fact measuring shades of subclinical psychopathy because the two constructs could not be separated in factor analyses, and they outperformed each other in terms of correlations with assumed core features of the respectively other construct (Blötner & Mokros, 2023). At the same time, evidence is thin with respect to gender invariance of extant measures of subclinical psychopathy (Spormann et al, 2023). Given that Blötner and Mokros' study was exclusively based on self-report data (posing a strong common method effect) and their sample was predominantly female (about 77%), it would be interesting to test in future research whether differences between scales on subclinical psychopathy and everyday sadism exist with respect to gender invariance.…”
Section: Everyday Sadism and Subclinical Psychopathymentioning
confidence: 99%
“…A recent study found that measures of everyday sadism are in fact measuring shades of subclinical psychopathy because the two constructs could not be separated in factor analyses, and they outperformed each other in terms of correlations with assumed core features of the respectively other construct (Blötner & Mokros, 2023). At the same time, evidence is thin with respect to gender invariance of extant measures of subclinical psychopathy (Spormann et al, 2023). Given that Blötner and Mokros' study was exclusively based on self-report data (posing a strong common method effect) and their sample was predominantly female (about 77%), it would be interesting to test in future research whether differences between scales on subclinical psychopathy and everyday sadism exist with respect to gender invariance.…”
Section: Everyday Sadism and Subclinical Psychopathymentioning
confidence: 99%